2007
DOI: 10.1089/neu.2007.0323
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Axonal Degeneration (“Dieback”) in the Corticospinal Tract after Transection Injury of the Rat Spinal Cord: A Confocal Microscopy Study

Abstract: Axonal dieback is a process in which axons in spinal tracts retract away from the initial site of injury. The purpose of this project is to study the dynamics of dieback in corticospinal tract (CST) axons after various time intervals post-injury, to find the optimal spatial-temporal window for regenerative treatment. Rats received transection injuries at the T8 spinal level and were sacrificed at different time periods (1, 2, 4, 8, and 16 weeks). Three weeks prior to sacrifice, DiI crystals were implanted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…Interestingly, although some conflicting results have been obtained, 50 different studies have consistently supported the inability of regenerating CST axons to enter into the injury site in different models of spinal cord injury such as contusion 10,51 and dorsal hemisection. [52][53][54][55][56] Altogether, these observations raise the possibility that axonal Ryk expression might not be restricted to CST axons and, therefore, that axons belonging to different tracts might be able to express this receptor after SCI. Nevertheless, it should be noted that in the injury model used to perform the present study, few CST axons were observed caudally to the lesion site, clearly indicating that several CST axons were spared after the induction of the damage.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, although some conflicting results have been obtained, 50 different studies have consistently supported the inability of regenerating CST axons to enter into the injury site in different models of spinal cord injury such as contusion 10,51 and dorsal hemisection. [52][53][54][55][56] Altogether, these observations raise the possibility that axonal Ryk expression might not be restricted to CST axons and, therefore, that axons belonging to different tracts might be able to express this receptor after SCI. Nevertheless, it should be noted that in the injury model used to perform the present study, few CST axons were observed caudally to the lesion site, clearly indicating that several CST axons were spared after the induction of the damage.…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, despite marked increase in local sprouting of the CST at points rostral to the lesion; we found no evidence of long-distance regeneration of the CST fibers toward and below the lesion site. This may be related to different factors, including the significant length of axonal die-back in the CST in the chronically injured spinal cord (Seif et al, 2007), the extended central cavity within the chronic lesion that dramatically disrupts the integrity of the CST (Thuret et al, 2006), the presence of myelin debris (Schwab and Bartholdi, 1996;Schwab, 2002Schwab, , 2004 and/or macrophages (Horn et al, 2008;Busch et al, 2009) that pose a barrier to regenerating axons around the lesion, and the residual CSPGs that have been unaffected by our ChABC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As axons of axotomized upper motoneurons progressively retract from the lesion site (Pallini et al, 1988;Seif et al, 2007) and often atrophy (Wannier et al, 2005), they may become less responsive to anti-Nogo-A treatment with increasing time after injury. In addition, scar formation and accumulation of CSPGs at the injury site may further impede successful regeneration (Busch and Silver, 2007), which could further reduce the efficacy of neurite growth-enhancing treatments.…”
Section: Introductionmentioning
confidence: 99%